Moisture sorption isotherms of dietetic Rabri at different storage temperatures. (11th July 2013) - Ghayal, Gajanan; Jha, Alok; Sahu, Jatindra K; Kumar, Arvind; Gautam, Anuj; Kumar, Ravindra; Rasane, Prasad
<x xml:space="preserve">Abstract</x> Moisture sorption isotherms of dietetic Rabri were determined at 10, 25 and 37 °C over a water activity range of 0.113–0.868. Sorption isotherms at 37 °C were sigmoidal (type II) curves, while at 10 °C, they were of type V and Type I at 25 °C for both adsorption and desorption processes. Five sorption models were tested to fit the experimental data. Halsey's model for 10 °C, Caurie's model for 25 °C and Modified Mizrahi's model for 37 °C were found to be the best fit. There was a clear hysteresis effect at 10 °C, whereas the effect gradually decreased and diminished at 37 °C.